Molecular basis of an agarose metabolic pathway acquired by a human intestinal symbiont - Benjamin Pluvinage (Nature Portfolio, 2018)
Polysaccharides are the primary structural cell wall and energy storage molecules of seaweed. Here, the authors show how the geographically restricted dietary polysaccharide agarose is selectively utilized by the human intestinal bacterium Bacteroides uniformis, providing insight into how carbohydrate metabolism evolves within the human microbiome.